Process Intensification: Nano-Carrier Formation by a Continuous Dense Gas Process - Beh, C.; Mammucari, R.; Foster, Neil (Elsevier BV, 2015)
Formation of nano-carriers such as vesicles and micelles using dense gas processing has been under extensive research for decades. Several dense gas processes have been developed to produce nano-carriers, most of them being batch processes. In the present study, a novel continuous dense gas, known as nano-carrier by a continuous dense gas (NADEG) process was developed as an evolution of a dense gas batch process known as the Depressurization of an Expanded Solution into Aqueous Media (DESAM) process. Transforming a batch process into a continuous process is a main aspect of process intensification. The NADEG process developed in this work enhances the production output of the batch process while producing nano-carriers free of harmful residual organic solvent. The NADEG process is a one-step process for the production of nano-carriers with lower size and higher encapsulation efficiency than the nano-carriers produced by other batch processes. Encapsulation efficiencies as high as 15% were achieved using liposomes to encapsulate a model hydrophilic compound (isoniazid) while encapsulation efficiencies of 10% were achieved in polymersomes for the same model compound.